The right of municipalities to differentiate market charge rates as an implementation of the local tax policy in Poland - Jacek Wantoch-Rekowski; Robert Kwaśniewski (Prawo Budżetowe Państwa i Samorządu)
Within the scope of the granted fiscal sovereignty, municipalities in Poland have the right to determine the amount of local taxes and charges within the limits specified in the statute. As the law currently stands, the provisions of the Act of 12 January 1991 on Local Taxes and Charges do not differentiate the rate of market charges, nor do they indicate the criteria which would constitute clear grounds for differentiation. As a result, doubts arise as far as the admissibility and limits for differentiating market charge rates at different market places in a given municipality, or the form of sale are concerned. The aim of the study is to determine the criteria for the admissibility of differentiation of market charge rates by a municipal council (in particular on various market places located in the municipality) and to indicate the limits for determining the amount of public and legal charges. The authors identify the criteria which allow municipalities to differentiate market charge rates and analyse the problem of the ban on differentiating market charge rates on the basis of the subjective criterion. The authors juxtaposed the issues examined in the study with theses that result from the current jurisprudence of administrative courts.